2004
DOI: 10.1074/jbc.m406179200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Biochemical, and Transcriptional Responses of Saccharomyces cerevisiae to the Novel Immunomodulator FTY720 Largely Mimic Those of the Natural Sphingolipid Phytosphingosine

Abstract: Sphingolipids are signaling molecules that influence diverse cellular functions from control of the cell cycle to degradation of plasma membrane proteins. The synthetic sphingolipid-like compound FTY720 is an immunomodulating agent in clinical trials for transplant graft maintenance. In this report, we compare the effects of the natural yeast sphingolipid phytosphingosine with FTY720 in Saccharomyces cerevisiae. We show that the multicopy suppressor genes that induce growth resistance to FTY720 also confer res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
2
30
0
1
Order By: Relevance
“…One simple way to elicit PHS accumulation is by preventing its catabolism. This can be achieved by adding N,N-DMS, a specific inhibitor of the first step (phosphorylation) of sphingoid base degradation (Welsch et al, 2004). Alternatively, the prevention of ceramide synthesis also results in PHS accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…One simple way to elicit PHS accumulation is by preventing its catabolism. This can be achieved by adding N,N-DMS, a specific inhibitor of the first step (phosphorylation) of sphingoid base degradation (Welsch et al, 2004). Alternatively, the prevention of ceramide synthesis also results in PHS accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…These membrane receptor proteins are well known to serve as transducers of various signals, but no examples have yet been described in which these proteins possess transporter activity. Rsb1 is localized to the plasma membrane and contains two N-linked glycosylation sites in its N terminus consistent with the topology expected for a 7-TM receptor protein (9).Work from several laboratories has demonstrated that increased function of the high affinity tryptophan transporter Tat2 influences PHS resistance (3,4,10). Because Rsb1 resembles a 7-TM receptor protein, we hypothesized that Rsb1 might * This work was supported, in whole or in part, by National Institutes of Health Grants GM75120 and GM49825 (to W. S. M.-R. 4 The abbreviations used are: LCB, long chain base; 7-TM, seven-transmembrane receptor protein; HePC, hexadecylphosphocholine; PHS, phytosphingosine; eGFP, enhanced GFP; ABC, ATP-binding cassette.…”
mentioning
confidence: 85%
“…Work from several laboratories has demonstrated that increased function of the high affinity tryptophan transporter Tat2 influences PHS resistance (3,4,10). Because Rsb1 resembles a 7-TM receptor protein, we hypothesized that Rsb1 might * This work was supported, in whole or in part, by National Institutes of Health Grants GM75120 and GM49825 (to W. S. M.-R. 4 The abbreviations used are: LCB, long chain base; 7-TM, seven-transmembrane receptor protein; HePC, hexadecylphosphocholine; PHS, phytosphingosine; eGFP, enhanced GFP; ABC, ATP-binding cassette.…”
mentioning
confidence: 99%
“…Welsch et al (40) showed that Saccharomyces cerevisiae cells respond similarly to FTY720 and phytosphingosine treatment, using single gene deletants and transcriptional profiling. Phytosphingosine is phosphorylated by Sphk2 but not Sphk1, whereas sphingosine and dihydrosphingosine are substrates for both Sphk1 and Sphk2 (2,36).…”
Section: Sbr Mutants Are Resistant To Endogenous Long Chain Bases-mentioning
confidence: 99%